The Reception of Society Towards Hoax News About the Covid-19 Pandemic on TikTok - Afdianto, Irfan; Abadi, Totok Wahyu (Indonesian Journal of Public Policy Review, 2023)
This research aims to analyze and explain the reception of society towards hoax news about the Covid-19 pandemic on TikTok. A quantitative descriptive method was employed, drawing on Jalaluddin Rahkmat's perception theory (1989:51). The study focused on the village of Cangkring Sidokare, with 96 respondents participating. The findings indicate that concerning the news item "Humans are test subjects," 79.2% of respondents considered it a hoax, while 20.8% regarded it as factual. Regarding the news item "Delayed menstruation after vaccination," 87.5% of respondents deemed it a hoax, with 12.5% considering it factual. Concerning the news item "Difficulties in conceiving after receiving the Tetanus vaccine," 85.4% of respondents viewed it as a hoax, while 14.6% considered it factual. Regarding the news item "Contents of the Sinovac vaccine," 86.5% of respondents considered it factual, with only 13.5% believing it to be a hoax. These findings shed light on the public's reception of hoax news on TikTok and emphasize the importance of addressing misinformation during the pandemic. Highlights: The study focuses on analyzing the public reception of hoax news about the Covid-19 pandemic on TikTok. A quantitative descriptive method is utilized, and 96 respondents from Cangkring Sidokare village are included. Findings indicate a significant percentage of respondents considering the analyzed news items as hoaxes, emphasizing the need to address misinformation during the pandemic. Keywords: Covid-19, Hoax News, TikTok, Public Reception, Perception Theory